Service attributes, customer satisfaction and return usage: A case of Uber Malaysia / Muhamad Zulhelmi Abdullah ...[et al.] - Abdullah Suhami, Muhamad Zulhelmi; Abdul Talib, Salim; Bachok, Sabaianah; Mohd Saleh, Maria (Universiti Teknologi MARA Selangor, 2018)
The transportation industry is one of the largest sectors in the global economy, and it changes in-tandem rapidly with the innovations of technology. Uber is one of the latest technology advancements in the transportation industry. The primary purpose of this study is to measure customer satisfaction level on the service attributes of Uber. Specifically, this study will address the issues of service attributes of Uber with customer satisfaction and return usage. The quantitative research approach was chosen to obtain the relevant data for this study which was conducted among Uber users who experienced Uber services at least once in Kuala Lumpur and Selangor. A total of 400 questionnaires were distributed to the users to allow for attrition rate from the sample size via google docs. The results of this study revealed that service attributes of Uber namely safety, price, convenience, and information and communications technology (ICT) do influence customer satisfaction and return usage. This study found that it is imperative for Uber operators to improve their services and provide better services that fit the current consumer demands on public transportation. In addition, ICT is crucial in transportation and tourism industry because it has a great impact on ensuring sustainable global and tourism development.